2019
DOI: 10.1111/jocd.13255
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of food consumption in patients with acne vulgaris and its relationship with acne severity

Abstract: Background Acne vulgaris is one of the chronic skin diseases with bacterial and perifollicular inflammation in its etiology. In recent years, numerous studies have been conducted on hormones and food consumption, which are thought to affect this inflammation. Aims In this study, how effective various possible factors such as food consumption habits and anthropometric measurement are in the etiology and severity of acne was investigated in patients with acne. Materials and Methods A case‐control study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
7
0
3
Order By: Relevance
“…The majority of case‐control studies evaluated the link between acne and dietary pattern 15‐30 and one the effects of the consumption of dairy products 31 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of case‐control studies evaluated the link between acne and dietary pattern 15‐30 and one the effects of the consumption of dairy products 31 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Akpinar et al . enrolled adults with acne and determined that, unlike fat intake consumption (calculated on the base of Body Mass Index), 3 days/week (2 weekdays and 1 weekend day) of high GI/GL carbohydrate‐rich food and of dairy products (one glass of milk, one bowl of yogurt, and a matchbox size of cheese) were promoting or exacerbating factors 23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that cheese and carbohydrate intake was higher in the acne group compared to the control group ( p < 0.05). In addition, they observed that cheese consumption increased acne formation and carbohydrate consumption increased severity, while fat consumption was not significant [ 32 ]. In a cross-sectional analysis of a large cohort of 24,452 participants in the French NutriNet-Santé study, showed that the consumption of fatty and sugary foods, sweet drinks, and milk was associated with acne in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between acne and diet, especially dairy consumption and taking high-glycemic-load diets, has been studied in recent years. Among various foods, dairy products and foods with a high-glycemic index have been found to be associated with acne development (9,10). The relationship between dairy intake and acne in adolescents and young adults has been widely studied in different countries.…”
Section: Introductionmentioning
confidence: 99%